Pengembangan Media Poly Game Dalam Pembelajaran Matematika Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SD - Riskiana Dewi, Nita; Wahyudi (CENDEKIAWAN, 2024)
Many students have difficulty in understanding math lessons with online learning, teachers need to be innovative in developing learning models and media that are different from learning in the classroom. This study aims to analyze the effectiveness of media development media poly game mathematics critical thinking ability grade V elementary school. The type of research used in the study is Research and Development (R&D). The development model in this study uses the ADDIE development model (Analysis, Design, Develop, Implement and Evaluate). Product testing uses the Experiment research type. The approach used in data analysis in development research. The use of questionnaire sheets as a data collection tool provides the basis for quantitative and qualitative analysis. Based on the results of the t test for the initial and final assessments, the Sig. (2-tailed) value of <.001. These results indicate that the Sig. (2-tailed) <0.05, then Ho is rejected and Ha is accepted. So, it can be concluded that the flat building poly game media is effective and feasible to use in improving critical thinking skills. This change in critical thinking increases student success, so that students more easily understand the material in the learning process and has a positive impact on student learning outcomes.